2017
DOI: 10.1089/apc.2016.0291
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Need for Third-Line Antiretroviral Therapy by Identifying Patients at High Risk for Failing Second-Line Antiretroviral Therapy in South Africa

Abstract: Although third-line antiretroviral therapy (ART) is available in South Africa's public sector, its cost is substantially higher than first and second line. Identifying risk factors for failure on second-line treatment remains crucial to reduce the need for third-line drugs. We conducted a case–control study including 194 adult patients (≥18 years; 70 cases and 124 controls) who initiated second-line ART in Johannesburg, South Africa. Unconditional logistic regression was used to assess predictors of virologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 36 publications
(33 reference statements)
5
30
0
Order By: Relevance
“…Living with a partner or family member was associated with a better virologic response, probably because social bonding has a strong influence over not feeling lonely or depressed, and adhering and responding better to medication [17]. Onoya et al in South Africa [18] observed that the risk of virologic failure was up to 5 times higher in non-adherence cases. Lee, et al, 2017 [19] reported that virologic failure after 6 months of ART is associated with a substantial risk of death.…”
Section: Plos Onementioning
confidence: 99%
“…Living with a partner or family member was associated with a better virologic response, probably because social bonding has a strong influence over not feeling lonely or depressed, and adhering and responding better to medication [17]. Onoya et al in South Africa [18] observed that the risk of virologic failure was up to 5 times higher in non-adherence cases. Lee, et al, 2017 [19] reported that virologic failure after 6 months of ART is associated with a substantial risk of death.…”
Section: Plos Onementioning
confidence: 99%
“…These relatively healthy patients may be less tolerant of ART-associated ADRs, which may reverse the recent gains made in retention in HIV treatment. Although access to ART has significantly improved, patients in resource-limited settings (including South Africa) still have few HIV treatment options beyond second-line ART, hence the need to closely monitor ART-related ADRs among patients receiving second-line ART [ 13 , 14 ]. However, the growth of the South African ART programmes was not followed by an equivalent growth in adverse event (AE) monitoring systems, and routine clinical data on ART AEs offers, at best, indicators of ART-associated ADRs.…”
Section: Introductionmentioning
confidence: 99%
“…Second-line ART only concerned a minority of patients, estimated at approximately 5.3% of all patients on ART in low-and middle-income countries (LMIC) in 2014 [2]. However, the need for second-line ART is forecast to grow in the coming years because of high firstline treatment failure rates, estimated at between 8 and 23% after 5 years [3]. This trend is expected to be reinforced by the growing demand for first-line ART following recent international guidelines recommending ART initiation irrespective of CD4 count [4].…”
Section: Introductionmentioning
confidence: 99%